The Use of Big Data in Pharmaceutical Clinical Development - Avasthi, Aditya; Telladarla, Lakshmi; Rajasagi, Gayatri (2013)
Pharmaceutical industry is working towards developing new tools that would help increase the efficiency of drug development while reducing the time and expenditure involved in research & development (R&D) and clinical trials. The lack of new blockbuster drugs and short patent periods is one of the key reasons the pharmaceutical industry is trying to reduce costs. Clinical trials absorb the major chunk of investment in the drug discovery and development process. One of the reasons most of the pharmaceutical companies are exploring the available opportunities to use Information Technology services is to improve the efficiency by gaining faster response while reducing the time and cost involved in clinical trials. Perceptive Informatics, a subsidiary of PAREXEL is a leading eClinical solutions provider that focuses on helping customers to increase the product development process through innovation. The solutions offered help their customers to maximize the benefits of clinical trial technologies by providing flexible software-as-a-service (SaaS) applications. The services offered by perceptive include Randomization and Trial Supply Management technologies, Medical Imaging, Clinical Trial Management Systems, Electronic Data Capture (EDC) etc. The solutions offered by Perceptive Informatics eClinical result in simplified workflow, improved efficiency, and enhanced productivity. Pharmaceutical Industry like the most of other industries is driven by customer choices, thus making it important for companies to understand customer’s choices and needs. Data analytics plays a key role in analysing and understanding customer behaviour and preferences. Pharmaceutical industry relies on past data for forecasting present and future trends about trials, thus it is important to have Big Data system that can store and analyse huge chunks of data. By using Big Data analytics solutions and specifically high performance analytics, companies can analyse huge amounts of data in seconds and minutes to reveal previously unseen patterns, sentiments and customer intelligence. Implementation of Cloud Computing can be a game changer move with futuristic point of view. This will enable availability of reliable data at a high speed on any device such as smartphones and tablets allows the company to take decisions faster, thus helping in enhancing the drug development process. The main objective of this report is to provide an understanding on how Perceptive Informatics can unlock the economic value of Big Data through the adoption of Big Data analytics. The scope of this report is to provide an insight into the key issues faced by pharmaceutical companies with respect to clinical trials, the role of Big Data analytics and business intelligence in optimizing costs across other industries and how Big Data is being utilized in clinical trials. This report also presents the approaches required to incorporate Big Data Analytics and Predictive Analytics for eClinical solutions. Further, we have provided Perceptive Informatics with recommendations on ways to leverage the advantages of Big Data analytics keeping in view the pros and cons of implementing the same.